On the Elasticity of Substitution between Labor and ICT and IP Capital and Traditional Capital - Vahagn Jerbashian (Global Labor Organization (GLO), 2024)
I estimate a nested CES production function for 9 European countries over 1996- 2020 using EU KLEMS data, distinguishing between information and communication technologies (ICT), intellectual property (IP) capital, and traditional capital. I assume that the aggregate output is produced using labor and these capital types and allow for differences in the elasticities of substitution between labor, an aggregate of ICT and IP capital, and traditional capital. The estimated elasticity of substitution between ICT and IP capital is strictly below one implying gross complementarity. ICT and IP capital together are gross substitutes for labor while traditional capital is a gross complement. The results imply that the fast pace of technological progress and accumulation in ICT and IP capital are responsible for almost the entire fall in labor income share. The imputed labor-aggregate capital elasticity exceeds 1, rising from 1996 to 2008 and falling afterward.
Keywords: E22; E25; J23; O33; 330; CES Production Function; Elasticities of Substitution; System of Equations; ICT; IP Capital; Traditional Capital